Isolation and Identification of Actinomycetes-A Potential Bioprospective Candidates - Bhagyasree S. R.; Mary Helen P. A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Actinomycetes were isolated from the vegetable decomposing soil sample by serial dilution agar plating method. Five actinomycetes (A1 to A5) were obtained and the antimicrobial activity was carried out by Kirby Bauer agar diffusion method against selected eleven bacterial and eight fungal pathogens. Actinomycete strain A4 demonstrated the most activity. The most active actinomycete strain (A4) was identified phenotypically as Streptomyces spp. using macroscopic and microscopic examination. Following that, bioactive substances were purified using silica gel column chromatography and identified using Gas Chromatography-Mass Spectrometry. The major compounds identified were canadaline (35.79%), 2’4-diphromophenoxyphenol(31.07%). The ethyl acetate crude extract was assayed for anticancer activity by MTT method on HepG2cells with 10µl of extract showed 48.93% viability of HepG2 cells and significantly (p-value 0.000151 < 0.05 α-values) active among different concentration of crude A4 extract. The crude extract of A4 actinomyces exhibited the maximum inhibition of 47.55% at 10 10µl concentration and the activity were significant (p-value 0.01485) <0.05 α-values. The DNA was isolated from actinomycete strain (A4) and the 16SrRNA gene was amplified using universal eubacterial 16SrRNA gene primers and it was genotypically identified as Streptomyces coelicolor.